Cyclic RGD-Functionalized pH/ROS Dual-Responsive Nanoparticle for Targeted Breast Cancer Therapy - Pu Yao; Xiaowen Wang; Qianmei Wang; Qing Dai; Yu Peng; Qian Yuan; Nan Mou; Shan Lv; Bangbi Weng; Yu Wang; Fengjun Sun (MDPI AG, 2023)
Breast cancer is the most common malignant tumor in women and is a big challenge to clinical treatment due to the high morbidity and mortality. The pH/ROS dual-responsive nanoplatforms may be an effective way to significantly improve the therapeutic efficacy of breast cancer. Herein, we report a docetaxel (DTX)-loaded pH/ROS-responsive NP that could achieve active targeting of cancer cells and selective and complete drug release for effective drug delivery. The pH/ROS-responsive NPs were fabricated using nanocarriers that consist of an ROS-responsive moiety (4-hydroxymethylphenylboronic acid pinacol ester, HPAP), cinnamaldehyde (CA, an aldehyde organic compound with anticancer activities) and cyclodextrin (α-CD). The NPs were loaded with DTX, modified with a tumor-penetration peptide (circular RGD, cRGD) and named DTX/RGD NPs. The cRGD could promote DTX/RGD NPs penetration into deep tumor tissue and specifically target cancer cells. After internalization by cancer cells through receptor-mediated endocytosis, the pH-responsive acetal was cleaved to release CA in the lysosomal acidic environment. Meanwhile, the high ROS in tumor cells induced the disassembly of NPs with complete release of DTX. In vitro cellular assays verified that DTX/RGD NPs could be effectively internalized by 4T1 cells, obviously inducing apoptosis, blocking the cell cycle of 4T1 cells and consequently, killing tumor cells. In vivo animal experiments demonstrated that the NPs could target to the tumor sites and significantly inhibit the tumor growth in 4T1 breast cancer mice. Both in vitro and in vivo investigations demonstrated that DTX/RGD NPs could significantly improve the antitumor effect compared to free DTX. Thus, the DTX/RGD NPs provide a promising strategy for enhancing drug delivery and cancer therapy.